Assessment of the Antibacterial Properties and Cytocompatibility of Implant Coatings Incorporating Antimicrobial Agents: An In vitro Study - Saloni Verma; Annuroopa Mahapatra; Kavita Gupta; Harisha Dewan; Minu Raju; D Anupama Prasad (Journal of Pharmacy and Bioallied Sciences)
Objective: This study evaluates the antibacterial efficacy and cytocompatibility of titanium implants coated with silver, chitosan, and antibiotics. Materials and Methods: Antibacterial properties were tested using inhibition zones against S. aureus, E. coli, and P. aeruginosa. The cytocompatibility was assessed through cell viability, adhesion, and proliferation by using human osteoblast-like cells (MG-63). Statistical analysis was performed using ANOVA and Tukey’s HSD test. Results: Antibiotics showed the highest antibacterial activity. Silver reduced cell viability, adhesion, and proliferation, while chitosan balanced antibacterial efficacy and biocompatibility. Time-dependent viability assays indicated consistent reduction for silver-treated cells. Conclusion: Silver, chitosan, and antibiotics are effective against implant-related pathogens, but their cytocompatibility varies.